Метод аналізу томографічних зображень грудної клітини пацієнтів з пневмонією - Ханнаві Алі (My University, 2020)
This work will help improve processing and analysis CT-images. It would also help to monitor the results of treatment of the diseases of organs of the chest. This module can be used in specialized clinics and diagnostic centres
Keywords: грудна клітина; легені; пневмонія; комп’ютерна томографія; бінаризація; сегментація; сегментація порогова